CORRELATION OF SIGNAL AVERAGED ECG PARAMETERS WITH ARTERIAL BLOOD PRESSURE IN HYPERTENSIVE PATIENTS - Riaz, Bushra; MA, Khan MA; S, Mubarak; M, Sarwar M (Pakistan Journal of Physiology, 2018)
Signal averaged ECG is a high resolution electrocardiography which detects ventricular late potentials in patients susceptible to ventricular arrhythmias. Ventricular late potentials are identified on the basis of three parameters detected on signal averaged ECG. This study was planned to determine the correlation of signal averaged ECG parameters with arterial blood pressure in hypertensive patients. Methods: Sixty-four patients with systemic arterial hypertension were enrolled in the study. Patients with acute or old myocardial infarction, diabetes mellitus, cerebrovascular accident, heart failure, structural heart disease, bundle branch block and cardiomyopathies were excluded from the study. DMS 300 4L Holter monitors were used to obtain 3 channel signal averaged ECG recording. CardioScan® premium luxury software was used for analysis of ventricular late potentials. Results: There were 49 male and 15 female patients (n=64) with mean age 60±11.83 years. Eleven patients (17.2%) had ventricular late potentials, whereas 53 (82.8%) were without them. The mean values for filtered QRS complex, low amplitude signals, root mean square voltage and noise were 108.52±23.63 ms, 28.81±20.78 ms, 92.17±51.02 mv and 0.29±0.25 mv respectively. Blood pressure was significantly and positively correlated with filtered QRS complex (p<0.001). The correlation with low amplitude signals and root means square voltage was not significant (p>0.05). Conclusion: Patients with higher systemic arterial blood pressure are at greater risk of developing ventricular late potentials which are reflective of ventricular arrhythmias. In hypertensive patients the arrhythmogenesis seems to be more related to duration of the cardiac signal compared to its voltage.